Supporting multitasking on the iPhone - Morrison, Michael, 1970- (O'Reilly breakdown., 2010)
"If you've been paying any attention at all to iOS 4 on the iPhone, you know multitasking is a big deal. But multitasking in an iPhone world isn't anything like multithreading or traditional multitasking. In this O'Reilly Breakdown, experienced iOS 4 programmer Mike Morrison explains what multitasking is, and teaches you how to get your own apps multitasking. You'll also build backward compatibility to support the still-huge number of devices that don't support multitasking."--Resource description page.